Effects of flavokawain a on Interleukin-6 and melanin productions in histamine-induced HaCat keratinocytes cells and mouse B16-F10 melanoma cells - Kim, Ji Man (2015)
Chronic skin inflammatory diseases affecting large populations in Malaysia and this condition is getting serious globally. Post-inflammatory hyperpigmentation (PIH) is one of chronic skin inflammatory diseases which usually resulted after inflammation process raises health, cosmetic and psychosocial concerns. Resultantly, anti-inflammatory and skin depigmenting agents have been developed to alleviate the effects thereof. However, current treatments on these diseases have potential toxicity and carcinogenicity. Therefore, there is a need to develop new anti-inflammatory and skin depigmenting agents with minimal side effects and greater efficacy. Chalcone derivatives is a group of compound belong to flavonoid family and has been reported with anti-inflammatory and anti-melanogenic properties. Thus study ought to determine the anti-inflammatory and anti-melanogrnic effects of the chalcone compound 1-(2-Hydroxy-4,6-dimethoxyphenyl)-3-(4-methoxyphenyl)prop-2-en-1-one (Flavokawain A, FLA) on cytokine production (Interleukin-6) in 10 μM histamine-induced HaCaT cells and melanin content in 10 μM histamine-induced mouse B16-F10 melanoma cells. The results showed that 50 μM of FLA suppressed the IL-6 production by 44% with HaCaT cell viability of 75%. Nevertheless, 50 μM of FLA was successfully reduced the melanin content by 73% with the B16-F10 melanoma cell viability of 78%. FLA showed high inhibitory activity towards melanin production in histamine-induced B16-F10 melanoma cells. This has indicates that FLA possess potential anti-inflammatory and anti-melanogenic activities. Thus, FLA has shown potential anti-inflammatory and depigmenting activities in vitro. Therefore, FLA might has the potential to be developed as an agent or alternative medicine to treat PIH. However, further studies need to be done to evaluate its efficacy and safety.